Ekplorasi Peran Dukungan Teman Sebaya dalam Membangun Kepercayaan Diri dan Kontribusi Mahasiswa Aktif Pendidikan Sosiologi FKIP Untirta - afsari, husniya; Afrizal, Stevany (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
The self-confidence that arises in students from the support of their peers greatlyinfluences their mental and emotional stability. Students who are confident tend tobe able to actively participate in class and campus activities. By participating inthese activities, students can enhance their academic and non-academic learningexperiences. This study aims to identify how peer support can build student selfconfidence on campus, as well as analyze this self-confidence in student involvementin academic and non-academic activities. Using a descriptive qualitative approachwith narrative analysis techniques through four stages: identifying narrativestructures, exploring the meaning behind coding narratives accompanied byanalysis for recurring themes, mapping story patterns, and reflection andinterpretation to reflect students' collective experiences. The results of this studyindicate that peer support in building self-confidence, active contributions in campusactivities and academic success plays a significant role both in active students ofsociology education, FKIP Untirta, during their studies and in the long term for theirfuture.Keyword: peers, students, self-confidence, active contribution